Enlargement of the human adrenal zona fasciculata and chronic psychiatric illness – an autopsy-based study. (2nd January 2020) - Busch, Johannes Rødbro; Lundemose, Sissel Banner; Lynnerup, Niels; Jacobsen, Christina; Jørgensen, Martin Balslev; Banner, Jytte
Abstract: Severe mental illness (SMI) is associated with a reduced life expectancy of up to 20 years. One possible contributor to this fact is dysregulation of the hypothalamus-pituitary-adrenal (HPA)-axis. Looking at the morphology of effector organs, such as the adrenal glands themselves, could reveal insights into organ function and response to possible HPA-dysregulation. This forensic autopsy-based study investigated if there were any morphological changes in adrenal glands between decedents who had previously been submitted to a psychiatric hospital with a diagnosis of schizophrenia ( n = 34), bipolar ( n = 5), or depressive disorder ( n = 20), any other psychiatric diagnosis ( n = 36) compared with decedents who had no previous psychiatric admission ( n = 40). Length of admissions to psychiatric wards and admission in the 180 days preceding death was included in regression as proxy variables for severity of illness. On the macroscopic level, we found no difference in gland weight or volume. On the microscopic level, we found a 25% increase in cross-sectional area of the zona fasciculata (ZF) in decedents who had a diagnosis of schizophrenia compared with controls ( p = 0.033). Other diagnosis groups did not differ from controls. Total admission length was positively correlated with area of the ZF. Lay Summary People with a severe mental disorder may be in a constant state of increased stress, which is harmful. This study looked at the adrenal gland, which produces stress hormones, to see if they were different in deceased persons who had suffered from a severe mental illness. We found that the part of the adrenal gland that produces stress hormones is larger in deceased patients who suffered from schizophrenia, but not other types of psychiatric illnesses, compared to deceased persons with no history of psychiatric illness.